The biological roles of CD24 in ovarian cancer: old story, but new tales - Gu, Yuanyuan; Zhou, Guannan; Tang, Xue; Shen, Fang; Ding, Jingxin; Hua, Keqin (Frontiers in Immunology, 2023)
CD24 is a glycosylphosphatidylinositol linked molecular which expressed in diverse malignant tumor cells, particular in ovarian carcinoma cells and ovarian carcinoma stem cells. The CD24 expression is associated with increased metastatic potential and poor prognosis of malignancies. CD24 on the surface of tumor cells could interact with Siglec-10 on the surface of immune cells, to mediate the immune escape of tumor cells. Nowadays, CD24 has been identified as a promising focus for targeting therapy of ovarian cancer. However, the roles of CD24 in tumorigenesis, metastasis, and immune escape are still not clearly demonstrated systematically. In this review, we i) summarized the existing studies on CD24 in diverse cancers including ovarian cancer, ii) illustrated the role of CD24-siglec10 signaling pathway in immune escape, iii) reviewed the existing immunotherapeutic strategies (targeting the CD24 to restore the phagocytic effect of Siglec-10 expressing immune cells) based on the above mechanisms and evaluated the priorities in the future research. These results might provide support for guiding the CD24 immunotherapy as the intervention upon solid tumors.